Message in a stainless steel bottle thrown into deep geological time - Lewandowski, M.; Kusiak, M.; Michalczyk; Szmigiel, D.; Sledziewska-Gojska, E.; Barzycka, B.; Wawrzyniak, T.; Luks, B.; Thordarson, T.; Wilde, Simon; Hoskuldsson, A. (Elsevier BV, 2017)
Â© 2017 The Authors In the 60th year after the placing of the corner stone under the Polish Polar Station at Hornsund (PPSH; Spitsbergen, Svalbard, Norway), a new capsule has been laid down in the vicinity of the PPSH. It is made of stainless steel, and includes five stainless steel containers, each carrying a message on different themes in our lives. The message is written in the language of objects, each of them speaking for itself. The capsule with containers has been buried in a 4.2 m deep hole, drilled for scientific purposes. The host rocks for the capsule are the Precambrian gneisses, representing the basement of the polar archipelago. We estimate that the capsule, now some 6 m a.s.l., will appear again on the surface after ca . 0.5 Ma, due to the combined effect of uplift and erosion. We also believe that it will be found, and the message understood, contrary to other messages sent by mankind into space.